2021
DOI: 10.1525/mp.2021.39.1.1
|View full text |Cite
|
Sign up to set email alerts
|

Does Timbre Modulate Visual Perception? Exploring Crossmodal Interactions

Abstract: Musical timbre is often described using terms from non-auditory senses, mainly vision and touch; but it is not clear whether crossmodality in timbre semantics reflects multisensory processing or simply linguistic convention. If multisensory processing is involved in timbre perception, the mechanism governing the interaction remains unknown. To investigate whether timbres commonly perceived as “bright-dark” facilitate or interfere with visual perception (darkness-brightness), we designed two speeded classificat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 69 publications
0
7
0
Order By: Relevance
“…Such integration involves both bottom-up (sensory-perceptual) and top-down (expectative) processes: on the one hand, a recipient perceives information using their senses; on the other, one integrates this information using previous knowledge and cognitive schemas stored in the long-term memory [82]. Other studies have already revealed that, under the influence of differently valenced soundtracks for the same video, not only do the viewers generate diverse plot expectations [20,83] and alter their recall of the scene [84,85] (i.e., high-level processing), but they can also be driven and even deceived in a way that impacts their visual perception (i.e., low-level processing) [18][19][20][21]. Therefore, it can be assumed that such a to-be-processed integration, only present in the music conditions, could be the cause of time overestimation in accordance with the memory-based model of time perception.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Such integration involves both bottom-up (sensory-perceptual) and top-down (expectative) processes: on the one hand, a recipient perceives information using their senses; on the other, one integrates this information using previous knowledge and cognitive schemas stored in the long-term memory [82]. Other studies have already revealed that, under the influence of differently valenced soundtracks for the same video, not only do the viewers generate diverse plot expectations [20,83] and alter their recall of the scene [84,85] (i.e., high-level processing), but they can also be driven and even deceived in a way that impacts their visual perception (i.e., low-level processing) [18][19][20][21]. Therefore, it can be assumed that such a to-be-processed integration, only present in the music conditions, could be the cause of time overestimation in accordance with the memory-based model of time perception.…”
Section: Discussionmentioning
confidence: 99%
“…As we will see, aside from the research traditionally focusing on music (i.e., perceived duration of musical excerpts), some work has pointed at the domain of audiovisual stimuli [15] and film-induced mood [16], with some interest in the dynamic interaction between the auditory (i.e., musical) and visual elements [17]. For example, it has been found that music is capable of modulating and altering visual perception [18][19][20] due to phenomena such as auditory driving [21].…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, general musical sophistication was found to correlate with self-reported music training ( Müllensiefen et al, 2014 ). As the students of the musical curriculum are chosen through aptitude tests based on imitation and recognition of rhythm, melody and pitch, we aimed to statistically control for pre-existing individual differences in musicality to better see the effect of music training, similarly to other studies where some Gold-MSI subscales were used as covariates ( Kang and Williamson, 2012 ; Farrugia et al, 2015 ; Ma et al, 2021 ; Wallmark et al, 2021 ; Krause et al, 2022 ).…”
Section: Methodsmentioning
confidence: 99%
“…In a series of two experiments, Wallmark et al ( 2021 ) asked whether the timbre of a musical note (an acoustic prime) would affect the subsequent visual perception of, in the first experiment, brightness (dark–bright dimension) and, in the second experiment, both brightness and spatial texture (smooth–rough dimension). To this end, they used a speeded-response paradigm in which the participants had to identify a shift in roughness/brightness between two consecutively-presented target squares of subtly contrasting levels (rougher/brighter, smoother/darker, or the same).…”
Section: Crossmodal Interactions In Roughness Perceptionmentioning
confidence: 99%
“…Moreover, strong differences might exist in the emotional response to felt textures depending on individual factors. However, Wallmark et al ( 2021 ) claim that the use of the term rough to talk about musical timbre and visual objects might be more than just be an arbitrary linguistic convention: “Perhaps we see brightness and spatial texture not just through eyes, but also (albeit faintly) through timbrally attuned ears” (p. 16). This drives us back at the core question at stake here, i.e., the possibility for intersensory, or amodal, stimuli quality to exist (see Spence & Di Stefano, 2022b ).…”
Section: Crossmodal Interactions In Roughness Perceptionmentioning
confidence: 99%